2018
DOI: 10.1007/s11882-018-0766-x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Allergens for Immunotherapy

Abstract: In-depth research in the field of allergen modifications as well as the advance of recombinant DNA technology have paved the way for improved diagnosis and research on human allergic diseases. A wide range of structurally modified allergens has been generated including allergen peptides, chemically altered allergoids, adjuvant-coupled allergens, and nanoparticle-based allergy vaccines. These modified allergens show promise for the development of AIT regimens with improved safety and long-term efficacy. Certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 122 publications
0
23
0
2
Order By: Relevance
“…16 Besides alternative routes of administration, the use of structurally modified allergens is also being investigated. 17,18 Cellular and Molecular Mechanisms of AIT Causes for the rising incidence of allergic disorders seem to be associated with increased urbanization. Reduced microbial exposure is associated with the development of allergy, which is mediated by dysregulated type 2 immunity and increased concentrations of allergen-specific IgE.…”
Section: Advances In Ait Routes-novel Approaches and Their Mechanismsmentioning
confidence: 99%
“…16 Besides alternative routes of administration, the use of structurally modified allergens is also being investigated. 17,18 Cellular and Molecular Mechanisms of AIT Causes for the rising incidence of allergic disorders seem to be associated with increased urbanization. Reduced microbial exposure is associated with the development of allergy, which is mediated by dysregulated type 2 immunity and increased concentrations of allergen-specific IgE.…”
Section: Advances In Ait Routes-novel Approaches and Their Mechanismsmentioning
confidence: 99%
“…This effort ultimately concluded that the allergenicity of a given protein could not be predicted on the basis of its stability and/or digestibility alone. These factors may contribute to overall allergenicity and can be useful in the design of superior allergen preparations for immunotherapy [ 37 ] (e.g., heated and ovomucoid-depleted egg white [ 38 , 39 ]). However, both the detection of food allergens in the bloodstream following oral ingestion [ 40 , 41 , 42 , 43 ], likely via absorption through the oral mucosa [ 43 ] and the discovery of the skin as a site for allergic sensitization in humans [ 44 , 45 , 46 , 47 ] imply that intact food allergens reach the immune surveillance system.…”
Section: On the Innocuousness Of Food Allergensmentioning
confidence: 99%
“…The disruption of IgE binding epitopes generates hypoallergenic derivatives which display very low IgE reactivity but conserve their capacity to generate IgG antibody and T cell responses. However, the mapping of the IgE binding epitopes, a key prerequisite step for such development, is challenging as they are mainly conformational . Alternative method consists of chemical modification of allergen extracts to derive allergoids with reduced allergenicity (their clinical efficacy is discussed in Chapter 9) …”
Section: Hypoallergenic Derivativesmentioning
confidence: 99%